Winners and losers: local perceptions of Kruger National Park's commercialisation process - Nyahunzvi, Dzingai K. (Centre for Recreation Research, 2016)
This paper explores through a neoliberal lens the implications of Kruger National Park‟s (KNP) “Commercialisation for conservation process” (hereafter the commercialisation process, for brevity‟s sake) that was launched in 2000. In doing so, the paper answers a clarion call for empirical research in this under-researched area of tourism-protected area partnerships in particular (Wilson, Nielsen & Buultjens, 2009) and the broader neoliberalisation of nature literature in general (Castree 2008a, 2008b; Himley, 2008). Note that the paucity of empirical studies of neoliberalisation globally (Heynen, McCarthy, Prudham, & Robbins, 2007) partially accounts for the existing hegemony of neoliberal development orthodox (King, 2009).